How do Social and Economic Rights Relate to Each Other in the Social Market Economy: An Introduction to this Special Issue - Frans Pennings (Utrecht University School of Law, 2019)
The term ‘social market economy’ was introduced in the Treaty on European Union in order to emphasise that social and economic objectives of the European Union are both important, and have to be reconciled with each other. This contribution describes how social objectives have been developed in EU law since the establishment of the European Economic Community. The Court of Justice of the European Union has interpreted Treaty provisions to give them maximum effect for the realization of these objectives. However, tensions with the economic objectives exist when economic freedoms are confronted with social rights. This contribution examines how the CJEU balances these interests, and how this relates to the social market economy. There are also areas where economic rights have no counterpart at the EU level, but where they interact with social policies of Member States. Here too, the concept of social market economy is relevant. After a discussion of these various dimensions of the term social market economy, the subsequent articles of this Special Issue are introduced.